The Civil War [compact disc] - Conan, Neal; Foote, Shelby; Doctorow, E. L., 1931-2015; Waterston, Sam; Holbrook, Hal; Stamberg, Susan, 1938-; McPherson, James M.; Horwitz, Tony, 1958-2019- (American chronicles (National Public Radio (U.S.)), 2011)
A century and a half later, the Civil War still resonates with all Americans. NPR captures the battlefield action, the human struggle, and the moral dilemmas of the war that pitted brother against brother, and family against family. From battlefield heroics to heart-wrenching letters home and in-depth profiles of complex characters, this outstanding soundscape is moving and enlightening. Includes expert commentary, gripping stories, and unforgettable voices.